THE DUTY OF UTMOST GOOD FAITH IN ASSET-FORFEITURE JURISPRUDENCE – SOME LESSONS TO LEARN - Nkululeko Christopher Ndzengu; John C von Bonde (Obiter, 2021)
The Constitutional Court has held that the provisions of the Prevention of Organised Crime Act 121 of 1998 that empower the State to apply ex parte for restraint and preservation orders regarding property involved in criminal activities do not per se violate the requirements of the audi alteram partem rule. However, the State still has to adhere to the normal procedural and other obligations imposed on applicants approaching courts for orders on an ex parte basis; one of these obligations is the duty of utmost good faith or uberrima fides. This article examines the application of this rule by SA courts. As respondents are diligent in seeking instances of nondisclosure of relevant information to warrant the application of the uberrima fides rule to their advantage, a high degree of openness and good faith is required from the State in order to avoid these ex parte orders being rescinded or discharged